The renunciation of perimeter area as a means of sanitation of the area, boundaries, and perimeter measurements of urban properties - Gonzales Loli, Jorge Luis (2021)
This article analyzes the regulation, operability, and efficiency of the registration procedure of «renunciation of area» as sanitation means incorporated through the CIX Plenary Session of the Registry Court of the National Superintendence of Public Registries. Doctrinal and jurisprudential aspects are highlighted regarding its regulation and practical utility, to evaluate its functionality and the possible need for regulatory enhancements. Previously, to achieve a better understanding of the issue, we will describe the most relevant aspects of the other sanitation procedures of areas, borders, and perimetric measurements that apply to urban properties in judicial, notarial, and registry proceedings.